EFEKTIVITAS PENGGUNAAN FITUR SALURAN BERITA WHATSAPP DI KALANGAN MAHASISWA JURNALISTIK UIN ALAUDDIN MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study aims to describe the use and effectiveness of the WhatsApp Channels feature among Journalism students at UIN Alauddin Makassar. The research is grounded in the Uses and Gratifications Theory to explore the respondents' motives, duration, and frequency of access. Effectiveness is measured using the Effectiveness Theory with five indicators: program comprehension, target accuracy, timeliness, goal achievement, and tangible change. This research applies a quantitative method through surveys or questionnaires distributed to 147 respondents. Data processing was carried out using descriptive analysis with the Statistical Package for the Social Sciences (SPSS) version 25.The results show that the majority of Journalism students use the WhatsApp Channels feature primarily to fulfill their need for information, indicating that most respondents utilize the feature to seek and obtain news and information. The average access duration is less than one hour per day, categorized as light viewers, with an access frequency of 1–3 times per day, indicating efficient and rapid information retrieval. The level of effectiveness in using this feature has an average score of 3.61, which falls into the effective category. This indicates that WhatsApp Channels are effectively used as a source of information for Journalism students. The implications of this study suggest that the WhatsApp Channels feature can serve as an effective news source for users. Future research may broaden the theoretical framework to explore additional factors influencing the effectiveness of this feature. Furthermore, content managers should consider developing the feature further to enhance its effectiveness in delivering news.